Sollicitudo omnium ecclesiarum: Kepedulian Dan Kerjasama Gerejawi Untuk Tanah Misi Dan Di Tanah Misi - Alphonsus Tjatur Raharso Tjatur Raharso (Seri Filsafat Teologi, 2020)
The concern to the situation and condition to all other members of the Church and the collaboration for the welfare of the entire Church is the expression of communio (communion) which is the character of Christ Church. The arise of Church in the mission land and its development which like the mustard seed is the fruit of the concern and collaboration of the missionaries showed by the community and Church which have been founded along the history. Considering Church resources are always limited, every form of across continents concern and collaboration should be done effectively. In the process of the evangelization in the mission land, these concern and collaboration encounter various forms of initiatives; starting from the simple, spontaneous, sporadic and individual to the consistent, coordinated organizations. These concern and collaboration often find frictions, conflicts of interest, impartialities, and injustice; especially concerning the implementation of the power of jurisdiction in the mission land and the submission to the superiority of the mission leaders. The negative excesses are seen and observed objectively and corrected to attain the more effective concerns and collaboration for the sake of the development of the mission work. The apostolic see is the central organ has explored and successfully founded an effective and sustainable missionary collaboration system, from the commissio to the mandate system. Nowadays, the missionary concern and collaboration across particular churches have not been centralized, but assigned to each local communities and particular Churches, to develop mutual collaboration according to the mutual need and projects through the written agreement to mutual minister